Porous Microrod Arrays Constructed by Carbon‐Confined NiCo@NiCoO2 Core@Shell Nanoparticles as Efficient Electrocatalysts for Oxygen Evolution. Issue 21 (6th April 2018) - Xu, Han; Shi, Zi‐Xiao; Tong, Ye‐Xiang; Li, Gao‐Ren
Abstract: The study of cost‐efficient and high‐performance electrocatalysts for oxygen evolution reaction (OER) has attracted much attention. Here, porous microrod arrays constructed by carbon‐confined NiCo@NiCoO2 core@shell nanoparticles (NiCo@NiCoO2 /C PMRAs) are fabricated by the reductive carbonization of bimetallic (Ni, Co) metal–organic framework microrod arrays (denoted as NiCo‐MOF MRAs) and subsequent controlled oxidative calcination. They successfully combine the desired merits including large specific surface areas, high conductivity, and multiple electrocatalytic active sites for OER. In addition, the oxygen vacancies in NiCo@NiCoO2 /C PMRAs significantly improve the conductivity of NiCoO2 and accelerate the kinetics of OER. The above advantages obviously enhance the electrocatalytic performance of NiCo@NiCoO2 /C PMRAs. The experimental results demonstrate that the NiCo@NiCoO2 /C PMRAs as electrocatalysts exhibit high catalytic activity, low overpotential, and high stability for OER in alkaline media. The strategy reported will open up a new route for the fabrication of porous bimetallic composite electrocatalysts derived from MOFs with controllable morphology for electrochemical energy conversion devices. Abstract : Porous microrod arrays (PMRAs) constructed by carbon‐confined NiCo@NiCoO2 core@shell nanoparticles (NiCo@NiCoO2 /C PMRAs) are designed and successfully fabricated by the reductive carbonization of bimetallic metal–organic frameworks and subsequent controlled oxidative calcinations in air. They exhibit superior electrocatalytic activity, low overpotential, and high stability for the oxygen evolution reaction in alkaline media.